Two new species of Viola (Violaceae) named in honor of preceding Peruvian botanists - Gonzáles, Paúl; Cano, Asunción (Phytotaxa, 2016)
We describe and illustrate Viola ferreyrae and Viola enmae (Violaceae), two new species of Viola section Andinium, both from the high Andes of southeastern Peru. Viola ferreyrae is named in honor of Ramón Ferreyra and Viola enmae in honor of Enma Cerrate, two Peruvian botanists who have greatly contributed to Peruvian botany. Viola ferreyrae is similar to Viola granulosa by its white flowers with purple lines and lack of a spur, but differs in having pinnatifid to pinnatipartite leaves, two pairs of stipules located at two different positions, and the upper surface of the leaf blade reticulate-alveolate (not granulose). Viola enmae is similar to Viola calchaquiensis by its small, crenulate and spathulate leaves, undulate crenulations, lacking stipules, upper and lateral petals oblong-obovate and reflexed, style apex truncated with margin trilobed, but differs in having blade narrowed, margins bearing 2(–3) undulate crenulations per side, bracteoles short, petals smaller, lateral petals smooth (not papillose-bearded), and lowermost petals somewhat emarginate.